Systematic Review of Surgical Treatment and Outcomes After Local Surgery of Primary Cutaneous Melanomas of the Penis and Scrotum. Issue 9 (September 2018) - Bittar, Julie M.; Bittar, Peter G.; Wan, Marilyn T.; Kovell, Robert C.; Guzzo, Thomas J.; Shin, Thuzar M.; Etzkorn, Jeremy R.; Sobanko, Joseph F.; Miller, Christopher J.
Abstract : BACKGROUND: Few data exist to guide surgical management and counseling about local recurrence after surgery of primary male genital melanoma. OBJECTIVE: To compile all available data on local recurrence rates after surgery of primary cutaneous melanoma of the penis and scrotum. MATERIALS AND METHODS: A systematic review of PubMed, Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Excerpta Medica database (EMBASE), and Web of Science identified all surgically treated penile and scrotal melanomas that reported local recurrence status and follow-up time. RESULTS: One hundred twenty-seven melanomas from 74 manuscripts were included. Eighty-six percent of melanomas were located on the penis, and 14% were located on the scrotum. Average follow-up time was 35.7 months. Scrotal melanomas were predominantly treated with organ-sparing surgeries (16/18, 88.9%), whereas penile melanomas were treated more often with amputation (61/109, 56.0%). Overall, local recurrence rate was 15.7% (20/127). Local recurrence rates for penile cases were 18.8% (9/48) after organ-sparing surgery versus 13.1% (8/61) for amputative surgery. Local recurrence rates were 66.7% (4/6) after positive surgical margins versus 10.2% (5/49) after negative surgical margins. CONCLUSION: Local recurrence rates are high after both organ-sparing and amputative surgery of primary cutaneous melanoma of the penis and scrotum. There is a need to standardize reporting for this rare tumor, as more complete data are necessary to develop consensus guidelines for surgical management of male genital melanoma. Abstract : Supplemental Digital Content is Available in the Text.